PENGARUH KUALITAS PELAYANAN DAN PENETAPAN HARGATERHADAP KEPUASAN KONSUMEN (Studi pada Star Foto Photography Pekanbaru) - Eko Bastian; Lie Othman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
The research was conducted at Star Foto Photography Pekanbaru, which is located on Jl. Garuda Sakti Km. 1, Pekanbaru, Riau in accordance with (copy of deed number 02. To determine the effect of service quality and pricing on customer satisfaction partially and simultaneously. This study used a quantitative descriptive analysis method with the SPSS 26 program. The population in this study were all consumers Star Photo Photography Pekanbaru in 2020 as well as a sample of 100 respondents from this study who were determined using the nonprobability sampling technique with the accidental sampling technique which was then formulated using the slovin formula.Data analysis used validity tests, reliability tests, simple linear analysis, multiple linear analysis, determination analysis and hypothesis testing with the t test and F test. The results of this study show the results of service quality and price affect consumer satisfaction, namely service quality affects customer satisfaction Then based on the F test, service quality and etermination prices affect consumer satisfaction simultaneously. Keywords: Service Quality, Pricing, Consumer Satisfaction